Surgically relevant anatomy of the axillary and radial nerves in relation to the latissimus dorsi tendon in variable shoulder positions: A cadaveric study. (February 2020) - Gates, Stephen; Sager, Brian; Collett, Garen; Chhabra, Avneesh; Khazzam, Michael
Background: The purpose of this study was to define the relationship of the axillary and radial nerves, particularly how these are affected with changing arm position. Methods: Twenty cadaveric shoulders were dissected, identifying the axillary and radial nerves. Distances between the latissimus dorsi tendon and these nerves were recorded in different shoulder positions. Positions included adduction/neutral rotation, abduction/neutral rotation for the axillary nerve, adduction/internal rotation, adduction/neutral rotation, adduction/external rotation, and abduction/external rotation for the radial nerve. Results: Width of the latissimus tendon at its humeral insertion was 29.3 ± 5.7 mm. Mean distance from the latissimus insertion to the axillary nerve in adduction/neutral rotation was 24.2 ± 7.1 mm, the distance increased to 41.1 ± 9.8 mm in abduction/neutral rotation. Mean distance from the latissimus insertion to the radial nerve was 15.3 ± 5.5 mm with adduction/internal rotation, 25.8 ± 6.9 mm in adduction/neutral rotation, and 39.5 ± 6.8 mm in adduction/external rotation. Mean distance increased with abduction/external rotated 51.1 ± 7.4 mm. Conclusions: Knowing the axillary and radial nerve locations relative to the latissimus dorsi tendon decreases the risk of iatrogenic nerve injury. Understanding the dynamic nature of these nerves related to different shoulder positions is critical to avoid complications.